Географиялық билим бериўде жойбарлаў (проект) технологияларын қолланыў (FAN va JAMIYAT, 2023)
The article reveals the importance of technology training, that is, based on project technology in the de- velopment of knowledge, skills and creative thinking of secondary school students when teaching geography.